Histoire et mouvements d’une collection de moulages du musée d’Ethnographie du Trocadéro, les bas-reliefs d’Abomey, Bénin, ex-Dahomey - Marlène-Michèle Biton (In Situ)
This article tries to track the history of a set of thirty-six molds which entered the collections of the former Musée d’Ethnographie du Trocadéro (Ethnographic Museum of the Trocadéro), in Paris. The latter was made in 1911 from a selection of Abomey (former Dahomey) royal palaces’ bas-reliefs, by Georges Waterlot, a colonial official in charge of the Dahomey printing-house, donator and correspondent in West-Africa for the museum. Waterlot’s work resulted in a publication in 1926 by the Institut d’ethnologie de l’université de Paris (Institute of Ethnology of the University of Paris). At that time, those molds presented the specificity of being copies in a museum supposed to exhibit original artifacts. However, the museum owned a multifunction molding workshop. The produced workpieces were designed to restoration, to the reproduction of originals remaining in the country such as pre-Columbian molds, to the representation of individuals embodying the diversity of human types and to the duplication of important workpieces (Cro-Magnon and La Ferrassie fossils, artworks from the Paleolithic period, such as the Venus of Lespugue) in order to help for scientific exchanges and get in return missing workpieces. The Waterlot’s moulds I found some sixty or seventy years later enabled, in 1989, while celebrating the « Centenial of King Glélé’s death » (King of Dahomey from 1858 to 1889), the reproduction of new workpieces that ran the opposite way this time, and enriched the collections of Beninese museums. This operation had a double appeal as it offered, on the one hand, copies of artworks in their early 20th century condition – that is to say shortly after the conquest – and on the other hand, it resurrected others that had disappeared long ago, thus restoring to this region’s cultural heritage what could not have been saved on the spot.